PENINGKATAN MUTU SARI BUAH NANAS DENGAN MEMANFAATKAN SISTEM FILTRASI ALIRAN DEAD-END DARI MEMBRAN SELULOSA ASETAT - Juansah, Jajang; Kiagus, Kiagus; Huriati, Farida (UI Scholars Hub, 2009)
Quality Improvement of Pineapple Juice using Filtration System of Dead-end Flow from Selulosa Asetate Membrane. The main idea of this research is determination of alternating food technology using acetate cellulose membrane. The Cellulose acetate membrane can be used to filter several solution like extract of pineapple. Filtration technique of dead-end flow system was used to improve the quality of pineapple extract. The filtration system was condition in a state of under pressure energy, gravity force and squealer velocity variation. Flux of membrane for all process treat to experience of degradation increasedly it time filtrasi. Assess got highest flux to process with squealer 22 cm/s and pressure equal to 1,021 x 105 Pascal. Assess obtained biggest rejeksi to process filtrasi without treating pressure and also squealer. Membrane which have been weared by process of filtrasi experience of event fouling. Result of screening with this filtration system show quality improvement, that is homogeneous mount, downhill turbidity, totalize dissolve solution (TPT), and the downhill viscosity. Assess prosentase of change of choiseness have got for the condensation yielded from process of filtration without treatment of emphasis and squealer. Others, at condensation yielded from treating experience of change assess pH which is not big. So that this condensation own best quality